Education Reform in Post-War Japan: An Interdisciplinary Analysis of Policies, Impact, and Historical Context (1945–1952) - Badawi, Habib (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This academic study examines the profound educational reforms that took place in post-war Japan from 1945 to 1952. The paper focuses on the transformative impact of the United States Education Mission on the Japanese education system during the Allied Occupation. The overarching objective of these reforms was to establish a democratic educational framework encompassing changes in administration, curriculum, textbooks, and teacher performance. This study sheds light on the historical context, policy implementation, and societal responses to these reforms. Additionally, it explores issues related to women's higher education during this transformative era, providing a comprehensive analysis of a pivotal chapter in Japan's history.